Ethnic differences in efficacy of drug treatment in patients with an acute manic episode: an individual patient data meta-analysis of randomized placebo-controlled trials - Bram W. C. Storosum; Sem E. Cohen; Cedrine A. Steinz; Taina K. Mattila; Carlijn C. Welten; Wim van den Brink; Kit Roes; Lieuwe de Haan; Damiaan A. J. P. Denys; Jasper B. Zantvoord (International Journal of Bipolar Disorders)
Abstract Background Little is known about the effect of ethnicity on drug treatment in patients with an acute manic episode. The aim of this study is to determine whether ethnicity moderates the response to drug treatment in patients with an acute manic episode, and whether this moderation is independent of potential confounders. Methods We analysed ten short-term placebo-controlled registration trials of atypical antipsychotics and anticonvulsive mood stabilizers in patients with an acute manic episode (n = 2199). A one-step random effects individual patient data meta-analysis (IPD) was applied to establish the moderating effect of ethnicity on symptom improvement on the Young Mania Rating Scale (Y)MRS and on response defined as 50% (Y)MRS symptom reduction. These analyses were corrected for baseline severity, age, and gender. A two-step IPD comparing these outcomes between White, Black and Asian patients. Additionally, a conventional meta-analysis was performed to determine the effect size of drug treatment separately for these ethnic groups. Results In the complete dataset, 60.4% of the patients was White, 8.0% was Black, 12.7% was Asian, 33.7% was of other ethnicities. Ethnicity did not significantly moderate the efficacy of drug treatment: pooled beta-coefficient (β) for the interaction between treatment and the ethnicities White, Black and Asian, varying from 0.889 to 0.899 with overlapping confidence-intervals ranging from 2.356 to 2.430 in the main analysis. The drug treatment effects were significant in all three analysable ethnicity groups compared to placebo. Discussion In White,Black, and Asian patients with an acute manic episode drug treatment is equally effective.